Seed treatment with salicylic acid invokes defence mechanism of Helianthus annuus against Orobanche cumana. (27th July 2016) - Yang, C.; Hu, L.Y.; Ali, B.; Islam, F.; Bai, Q.J.; Yun, X.P.; Yoneyama, K.; Zhou, W.J.
Abstract: The root holoparasitic angiosperm sunflower broomrape ( Orobanche cumana ) specifically affects sunflower ( Helianthus annuus ) growth and causes severe damage all over the world. This investigation was designed to examine the protective effects of salicylic acid (SA) treatment to the seeds of an O. cumana ‐susceptible cultivar of sunflower (TK0409). Sunflower seeds were pretreated with different concentrations (0, 0.5 and 1 mM) of SA and inoculated with O. cumana for 4 weeks. O. cumana infection resulted in reduction in plant biomass, endogenous SA level, and the expression of SA‐related genes including pal, chs and NPR1 . By contrast, O. cumana infection enhanced the production of reactive oxygen species, activities of antioxidant enzymes as well as contents of phenolics and lignin. Seed treatment with 1 mM SA increased sunflower biomass in terms of plant height, fresh weight and dry weight by 10%, 13% and 26%, respectively, via reducing the number and biomass of established O. cumana . The increase of hydrogen peroxide contents by 14% in the 1 mM SA treated sunflower plants appeared to be because of the inhibition of ascorbate peroxidase and catalase by exogenous SA. The enhanced expression of pathogenesis‐related genes ( PR3 and PR12, encoding chitinase and defensin, respectively) after 4 weeks of inoculation indicated that systemic acquired resistance was induced in the SA treated sunflower in which the level of endogenous SA was also elevated in a dose‐dependent manner. The increased expression of a hypersensitive‐responsive (HR) gene hsr indicated that the resistance of sunflowers might be associated with a hypersensitive reaction which was activated by exogenous SA treatment.